Classification of final exam questions in the reading subject based on Bloom's taxonomy: Applied in Al-Raya University - Makmur, Reinizqy Mughniza; El Warfali, Sulaiman Hassan Sulaiman; Smeer, Zeid B (Abjadia : International Journal of Education, 2025)
This study analyzes final exam questions for a reading course using Bloom's Taxonomy to evaluate their alignment with cognitive learning objectives. A descriptive-analytical approach was employed, with data collected from exam questions at Al-Raya University Institute and supplemented by literature and online sources.  Findings reveal an emphasis on understanding (36 questions, 43 points) and application (17 questions, 24 points), demonstrating strong comprehension and practical skills. However, lower scores in analysis (9 questions, 11 points), evaluation (1 question, 1 point), and creation (5 questions, 17 points) highlight challenges in higher-order thinking.  The results suggest the need for more balanced assessments to foster comprehensive cognitive development, providing valuable insights for improving evaluation strategies in reading education.